Free trade: Roadmap for US-ASEAN ties - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
In the past decade, the Association of Southeast Asian Nations (ASEAN) has evolved as a regional hub in Asian regionalism due to the bloc’s Free Trade Agreements (FTAs) with major economies in the Asia Pacific. Yet, the US remains the only Pacific power that has not initiated any form of formal FTA with ASEAN.